Suitable split nitrogen application increases grain yield and photosynthetic capacity in drip-irrigated winter wheat (Triticum aestivum L.) under different water regimes in the North China Plain - Hamani, Abdoul Kader Mounkaila; Abubakar, Sunusi Amin; Si, Zhuanyun; Kama, Rakhwe; Gao, Yang; Duan, Aiwang (Frontiers in Plant Science, 2023)
Chemical fertilizer overuse is a major environmental threat, critically polluting soil and water resources. An optimization of nitrogen (N) fertilizer application in winter wheat (Triticum aestivum L.) in association with various irrigation scheduling is a potential approach in this regard. A 2-year field experiment was carried out to assess the growth, yield and photosynthetic capacity of drip-irrigated winter wheat subjected to various split applications of urea (240 kg ha−1, 46% N). The eight treatments were, two irrigation scheduling and six N application modes in which, one slow-release fertilizer (SRF). The two irrigation scheduling were I45 (Irrigation scheduling when ETa-P reaches 45 mm) and I30 (Irrigation scheduling when ETa-P reaches 30 mm). The six N levels were N0-100 (100% from jointing to booting), N25-75 (25% during sowing and 75% from jointing to booting), N50-50 (50% during sowing and 50% from jointing to booting), N75-25 (75% during sowing and 25% from jointing to booting), N100-0 (100% during sowing), and SRF100 (240 kg ha−1, 43% N during sowing). N top-dressing application significantly (P <0.05) inﬂuenced wheat growth, aboveground biomass (ABM), grain yield (GY) and its components, photosynthetic and chlorophyll parameters, and plant nutrient content. According to the averages of the two winter wheat-growing seasons, the I45N50-50 and I45SRF100 treatments, respectively had the highest GY (9.83 and 9.5 t ha−1), ABM (19.91 and 19.79 t ha−1), net photosynthetic rate (35.92 and 34.59 µmol m−2s−1), stomatal conductance (1.387 and 1.223 mol m−2s−1), SPAD (69.33 and 64.03), and chlorophyll fluorescence FV/FM (8.901 and 8.922). The present study provided convincing confirmation that N applied equally in splits at basal-top-dressing rates could economically compete with the costly SRF for winter wheat fertilization. The I45N50-50 treatment offers to farmers an option to sustain wheat production in the NCP.